Sex‐specific effects of PET‐MPs on Drosophila lifespan. Issue 3 (4th May 2022) - Liang, Boying; Zhang, Dake; Liu, Xingyou; Xu, Yifan; Tang, Hao; Li, Yan; Shen, Jie
Abstract: In recent years, as an emerging pollutant, microplastic (MPs) pollution is gradually becoming a research hotspot. MPs are ubiquitous in the entire ecological environment. Organisms can be exposed to MPs via inhalation or ingestion. In view of the widespread of MPs pollution, the impact of MPs on biology should be further investigated. In previous experiments, we have conducted research on the physiology of Drosophila exposed to polyethylene terephthalate microplastics (PET‐MPs). However, will the lifespan of Drosophila be affected under long‐term PET‐MPs exposure? The analysis of variance analysis of our experimental results indicates that there are significant differences between males and females, F (1, 895) = 68.19, p  < 0.001, between PET‐MPs concentration, F (3, 895) = 8.11, p  < 0.001. There are also significant interactions between sex and MP concentration, F (3, 895) = 4.00, p  < 0.01. For Cox and log‐rank test, 1 g/L of PET‐MPs prolongs the lifespan of male flies. The reason for this phenomenon may be the hormesis effect. Abstract : Polyethylene terephthalate microplastics (PET‐MPs) have sex‐specific effects on the lifespan of flies. PET‐MPs at the concentration of 1 g/L extend the lifespan of male flies. The synergistic effects of MPs' interaction with additives and pollutants deserve further investigation. Highlight: Long‐term exposure of polyethylene terephthalate microplastics (PET‐MPs) has sex‐specific effects on the lifespan of Drosophila . The effects of PET‐MPs are different depending on concentrations. The synergistic effects of MPs with additives and pollutants worth further exploration.